Electronic Medical Record Design to Enhance Hospital Performance (Case Study JAVACARE Hospital) - Nugraha, Andri Bagus; Basri, Mursyid Hasan (The Indonesian Journal of Business Administration, 2014)
Abstract. In terms of obtain accreditation from Joint Commission International (JCI) and fulfill the government’s Minimum Service Standards (SPM), JAVACARE Hospital should perform several improvements in their business process especially in process integration.In this final project, the problem identification is using Current Reality Tree (CRT) method. The result of this method is shows that there’s no integrated system could raise the problems such as coordination problem between doctors in patient handling, coordination between doctor and medical record coder in term of pricing, and reporting problem which caused by long time to gather the data or the data is not even exists. Those problems will affect the hospital accreditation from JCI and SPM fulfillment.The objective in this final project is to facilitating the hospital with designing electronic medical record system which integrated with the other process in the hospital. The system type is Executive Information System. Performance measurement hospital also designed which using Integrated Performance Measurement System (IPMS) that developed by Dermawan Wibisono.. IPMS will become a framework to map the SPM performance variables, determine the weight of the variables, and find the linkage between the variables. So that, The Electronic Medical Record will become facilitator for user to input the data and those data will be measured and shown in performance dashboard. The expected result in this final project is with the implementation of Electronic Medical Record can integrating the hospital processes, improving hospital performance and real-time monitoring the hospital performance.